2019
DOI: 10.1088/1748-9326/ab28ba
|View full text |Cite
|
Sign up to set email alerts
|

Passive survivability of buildings under changing urban climates across eight US cities

Abstract: In the US, more than 80% of fatal cases of heat exposure are reported in urban areas. Notably, indoor exposure is implicated in nearly half of such cases, and lack of functioning air conditioning (AC) is the predominant cause of overheating. For residents with limited capacity to purchase, maintain, and operate an AC system, or during summertime power outages, the ability of buildings to maintain safe thermal conditions without mechanical cooling is the primary protective factor against heat. In this paper, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(17 citation statements)
references
References 62 publications
(65 reference statements)
0
17
0
Order By: Relevance
“…48,49 Such high temperature and humidity combinations have not been reported in any major global heat extreme event between 2007 and 2019 (figure 2), but the translation of outdoor (landscape and urban level) conditions to the indoor environment is heavily dependent on characteristics at the building level of the heat cascade. 58 Very high air temperatures (>45°C) are usually accompanied by lower humidity (figure 2). Because most sweat readily evaporates without sup plemental airflow in these conditions, fan use worsens physiological heat strain 47 and should not be recom mended.…”
Section: Individual Levelmentioning
confidence: 99%
“…48,49 Such high temperature and humidity combinations have not been reported in any major global heat extreme event between 2007 and 2019 (figure 2), but the translation of outdoor (landscape and urban level) conditions to the indoor environment is heavily dependent on characteristics at the building level of the heat cascade. 58 Very high air temperatures (>45°C) are usually accompanied by lower humidity (figure 2). Because most sweat readily evaporates without sup plemental airflow in these conditions, fan use worsens physiological heat strain 47 and should not be recom mended.…”
Section: Individual Levelmentioning
confidence: 99%
“…The risk of major and widespread power outages that affect a large number of customers and that would result in "heat disasters" appears to be growing [19]. Research has shown that the summertime overheating of residential buildings may increase by upwards of 25% by the middle of the 21st century [20].…”
Section: Introductionmentioning
confidence: 99%
“…Hotter and more humid air masses in uence subtropical and tropical climate areas more than other climates [24]. In these areas, indoor environments without an adequate cooling system can cause indoor overheating [25]. In Florida, statewide average temperatures are higher than 30 degrees Celsius during the summer, and some residents lack AC units to manage cool indoor environments.…”
mentioning
confidence: 99%